The Adaptability of Different Wheat Varieties to Deep Sowing in Henan Province of China - Cheng Yang; Rongkun Wang; Cheng Tian; Deqi Zhang; Hongjian Cheng; Xiangdong Li; Baoting Fang; Haiyang Jin; Hang Song; Baoming Tian; Fang Wei; Ge Yan (Agronomy)
Appropriate deep sowing holds significant potential in enhancing wheat production, particularly in dry and low-rainfall regions. Henan Province is a major winter wheat-producing area in China; evaluating the adaptability of wheat varieties to deep sowing through scientific methods is crucial to improve wheat production. This study investigates 26 wheat cultivars in Henan. By assessing key traits of seeds and seedlings at various sowing depths, we analyzed the effects of sowing depth on seed germination and seedlings. A comprehensive index for deep sowing tolerance was established using principal component analysis (PCA) and the membership function method, followed by the classification of the varieties according to their tolerance to deep sowing. The results indicated that, with increased sowing depth, seedling emergence time, coleoptile length, and coleoptile internode length increased, while seedling emergence rate, seedling height, leaf area, and shoot dry weight per unit area decreased. Based on PCA and membership function values, the 26 wheat varieties were classified into three categories: deep sowing tolerant, moderately tolerant, and intolerant, comprising 3, 19, and 4 varieties. This study provides valuable insights for optimizing wheat variety selection and improving sowing practices in Henan Province, offering both theoretical and practical contributions to local wheat production.